The role of the line manager in promoting well-being and capability in specialist unit ambulance personnel - Leather, Christopher (2016)
The impact of line manager (supervisor) behaviour on employee well-being, work attitudes, performance and perceptions of organizational culture are assessed using a sample of specialist unit (S-Unit) ambulance personnel. Underpinning line manager behaviour was a 10 item, two-factor structure: supportive (six items) and unsupportive (four items) manager behaviour (see chapter 3). Analysis of manager behaviour on outcome variables was performed using cross-sectional (n = 473) and longitudinal, matched-cases, analysis (n = 242). Cross-sectional analysis (see chapter 5) revealed that supportive manager behaviour was significantly related to increased proximal and distal collective capability, individual capability (efficacy; see chapter 4), work engagement, attitudes towards patient care, organizational commitment, perceived organizational support and job satisfaction; and negatively related to symptoms of ill-health, burnout and intentions to quit. Unsupportive manager behaviour was observed to be significantly related to increased symptoms of ill-health and burnout. It was also found to be marginally related to symptoms of post-traumatic stress disorder. Longitudinal analysis (see chapter 6) revealed that supportive manger behaviour was linked to greater proximal collective capability and reduced intentions to quit. Unsupportive manager behaviour was found to be significantly related to increased reporting of symptoms of post-traumatic stress disorder and ill-health. Reverse causality testing was employed on the longitudinal data and results showed that symptoms of ill-health may influence perceptions of unsupportive manager behaviour. The factor structure of manager behaviour is discussed and relationships (significant and non significant) are assessed against other research.